Sustainable Chicken Waste Product Selection Using a Hybrid CRITIC–MARCOS-Based Decision Support System - Nurmaliana Pohan; Aditya Widodo; Arlan Tri Handika; Cindy Afriana Jambak; Hari Prayudha; Rayhan Atricha Rambe (Sistem Pendukung Keputusan dengan Aplikasi, 2026)
The growth of the poultry industry has led to an increase in chicken waste volume, which may cause environmental and health problems if not properly managed. However, chicken waste also has the potential to be processed into value-added products that support sustainable agriculture and a circular economy. This study aims to develop an objective and systematic decision support system to determine the most sustainable chicken waste product based on economic efficiency and environmental impact within the operational context of the Agricultural Modernization and Assembly Agency (BRMP) of North Sumatra. A hybrid Multi-Criteria Decision Making (MCDM) approach was applied by integrating the Criteria Importance Through Intercriteria Correlation (CRITIC) method and the Measurement of Alternatives and Ranking according to Compromise Solution (MARCOS) method. The CRITIC method determines criteria weights objectively based on data variability and inter-criteria correlation, while the MARCOS method ranks alternatives based on utility values relative to ideal and anti-ideal solutions. Fifteen chicken waste product alternatives were evaluated using seven economic, technical, and environmental criteria. The results show that chicken manure compost is the best alternative, with the highest utility value (Kᵢ > 1), indicating superior performance in terms of production cost, market feasibility, environmental impact, and raw material availability. Sensitivity analysis confirms that the ranking results remain stable despite changes in criteria weights. This study contributes to the development of hybrid MCDM methods for agricultural waste management and provides a transparent and reliable decision-making framework for policymakers.